COMPARATIVE PROFILING OF BIOMARKER PSORALEN IN ANTIOXIDANT ACTIVE EXTRACTS OF DIFFERENT SPECIES OF GENUS FICUS BY VALIDATED HPTLC METHOD - Alam, Perwez; Basudan, Omer A.; Alqasoumi, Saleh I.; Abdel-Kader, Maged S.; Donia, Abd El Raheim M.; Al-Rehaily, Adnan; Alam, Prawez; Siddiqui, Nasir A.; Shakeel, Faiyaz (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: A simple but sensitive HPTLC method was developed for the comparative evaluation of psoralen in antioxidant active extracts of leaves of five different species of genus Ficus (Ficus carica, Ficus nitida, Ficus ingens, Ficus palmata and Ficus vasta). Materials and Methods: HPTLC studies were carried out using CAMAG HPTLC system on Glass-backed silica gel 60F254 HPTLC pre-coated plates using selected mobile phase toluene: methanol (9:1). The antioxidant activity was carried out, using DPPH free radical method. Results: Among all the five species of genus Ficus, F. palmata and F. carica exhibited comparatively good antioxidant activity in DPPH assay. The developed HPTLC method was found to give a compact spot for psoralen (Rf = 0.55±0.001) at 305 nm. The regression equation and r2 for psoralen was found to be Y= 4.516X+35.894 and 0.998. The quantification result revealed the presence of psoralen in only two species, F. carica (0.24%, w/w) and F. palmata (1.88%, w/w) which supported their supremacy for anti-oxidant potential over other species. The statistical analysis proved that the developed method was reproducible and selective. Conclusion: The developed method can be used as an important tool to assure the therapeutic dose of active ingredients in herbal formulations as well as for standardization and quality control of bulk drugs and in-process formulations. This method can also be employed for the further study of degradation kinetics and determination of psoralen in plasma and other biological fluids.